NILAI-NILAI PENDIDIKAN KARAKTER DALAM AL-QUR’AN SURAT AL-AN’AM AYAT 151-153 DAN IMPLEMENTASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - SUHARTO SUHARTO (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
Character education has become an interesting issue to discuss among education practitioners lately. This is because the world of education has so far been seen as constrained by absolute interests. Only concerned with intellectual intelligence, reason and reasoning without being accompanied by an intensive development of intellect in the heart, feelings and emotions or what is often known as character education. This research was conducted at SMK Negeri 1 Cilegon. This type of research is a qualitative field research. Data collection techniques using observation, interviews, documentation. The methodical approach uses study analysis by examining all the data obtained by the author from various sources using semantic analysis and observation. This study uses theory According to D. Yahya Khan,